Archaic Vocabulary In The Aceh Language Dictionary The Works Of Aboe Bakar And Friends - Safriana; Safriandi; Iba Harliyana (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This research is entitled "Archaic Vocabulary in the Aceh Dictionary the Works Aboe Bakar and Friends". This study aims to find out what has been archaic in the Aceh Language Dictionary by Aboe Bakar and his friends. The approach used in this research is quantitative. The data collection in this study was using a questionnaire given to respondents from the categories of adolescents (15-20) years, adults (21-45) years and the elderly (46-65) years. The source of the data for this research is the native Aceh language, the researchers chose two sub-districts in Lhokseumawe City, namely Banda Sakti sub-district and Muara Dua sub-district. The researcher found that there were already archaic Acehnese vocabularies, as many as 148 vocabularies, namely abeusi, abeueng-abeueng, abiek, abin, acan, abôk. acok, asôb, 'aduat, akok, akô, 'ala/'akla, alang, alén, alét, bahie, bakeusih, bakai, baki, bako, balah, balak, balo, baloe, balôh, baluem, bandôt, bangkéh, bantaban, barah, baréng, basoe, basôh, bateue, baweue, bawôih, beuaih, bleutèe, beung'u, beupak, bijoe, beureu ôn, beuténg, beutôh, bhak, bhong, biduen, biheue, bingkéh, can'ok, cawöi, dabèe, daih, dampéng, darôi, dudom, dugom, deumpék, dangdhöt, dapa/dapha, dawok, deuru, dung'ok, èeng-èeng, èekeulaih, èekheutieue, èejeuba, gubra, ganong, geuny'ie, gumoe, guntoe, guroe, haleumab, haling, hanggô, hangèek, hany'ang, hareutoe, harôih, harok harök, hilam, himpôn, hiram, hirö, idan-idan, ilat, ingkang, meu (ingkang), ingoih, iréh, jaban, jaja, jagon jagön, kancôt, keubeueng, keudöt, keululu, keureukôih, keutupéng, kinca, kiwieng, laböh, labon/labön, lamb.